Analysis of T-cell responses in metastatic melanoma patients vaccinated with dendritic cells pulsed with tumor lysates - Griffioen, Marieke; Schadendorf, Dirk (Cancer immunology immunotherapy, 2004)
In melanoma patients, CD8+ cytotoxic T cells have been found recognizing self-proteins of which the expression is restricted to the melanocytic lineage. These melanocyte differentiation antigens are expressed in normal melanocytes as well as in 80-100% of primary and metastatic melanoma. In this report, six HLA-A*0201-subtyped metastatic melanoma patients vaccinated with dendritic cells (DCs) pulsed with autologous tumor lysates and keyhole limpet hemocyanin (KLH) were screened for the presence of CD8+ T cells specific for three HLA-A*0201-binding peptides derived from the melanosomal antigens MART-1/Melan-A, gp100, and tyrosinase. For this purpose, nonstimulated as well as in vitro peptide-stimulated peripheral blood mononuclear cells (PBMCs) were tested for peptide-specific IFN-γ release by enzyme-linked immunosorbent spot (ELISpot) assays. Furthermore, expression of the melanosomal antigens MART-1/Melan-A, gp100, and tyrosinase in tumor lesions was analyzed by immunohistochemistry before and after vaccination. We also used the ELISpot technique to investigate whether KLH-specific T cells were induced and whether these cells released type 1 (IFN-γ) and/or type 2 (IL-13) cytokines. Our data show induction of CD8+ T cells specific for the melanosomal peptides MART-1/Melan-A27-35 or tyrosinase1-9, as well as IFN-γ-releasing KLH-specific T cells, in two of six vaccinated melanoma patients, but do not support an association between the induction of these T cells and clinical responses.
Gesehen am 25.11.2020